2022
DOI: 10.1021/acs.biochem.2c00037
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Conservation Does Not Always Signify a Functional Imperative as Observed in the Nitroreductase Superfamily

Abstract: Consensus sequences have the potential to help classify the structure and function of proteins and highlight key regions that may contribute to their biological properties. Often, the level of significance will track with the extent of sequence conservation, but this should not be considered universal. Arg and Lys dominate a position adjacent to the N1 and C2 carbonyl of flavin mononucleotide (FMN) bound in the proteins of the nitroreductase superfamily. Although this placement satisfies expectations for stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…2 and 3 ; Supplementary Method 1 ), which show that all NMN + first shell residues are highly conserved. However, studies have shown that caution should be taken in equating sequence consensus to functional essentiality 42 , especially when the desired function (i.e., NMN + -utilizing activity) has not been explored by evolution. Instead of bioinformatic analysis, we next relied on a structure-guided approach (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2 and 3 ; Supplementary Method 1 ), which show that all NMN + first shell residues are highly conserved. However, studies have shown that caution should be taken in equating sequence consensus to functional essentiality 42 , especially when the desired function (i.e., NMN + -utilizing activity) has not been explored by evolution. Instead of bioinformatic analysis, we next relied on a structure-guided approach (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%